Clarifying the taxonomy of Gymnodinium fuscum var. rubrum from Bavaria (Germany) and placing it in a molecular phylogeny of the Gymnodiniaceae (Dinophyceae). Issue 2 (17th February 2020) - Romeikat, Corinna; Knechtel, Johanna; Gottschling, Marc
Abstract : The taxonomy of Gymnodinium and the Gymnodiniaceae is inconsistent, because the systematic position of the type species, G. fuscum, is elusive at present. Historical names of microscopic species are frequently ambiguous, making reliable determination difficult, although it is crucial to fully explore the biology of the organisms. We collected material at the type locality of a historical variety, namely Gymnodinium fuscum var. rubrum, var. nov., and established a strain for morphological and molecular studies. The motile cells showed a characteristically obovate shape in outline, with acute antapex, and a horseshoe-shaped apical structure complex, which is characteristic for many Gymnodiniaceae. Older cultivated material further exhibited red granules in the cell, being the name-giving diagnostic character of the variety. In a molecular phylogeny, monophyletic Gymnodiniaceae segregated into seven clades at high taxonomic level. The phylogenetic resolution of the molecular DNA-tree provides evidence for a dynamic evolutionary scenario of Gymnodiniaceae and might prove helpful for an improved classification of the group. As the taxonomic result, we validate and epitypify the historical name, G. fuscum var. rubrum, var. nov., showing diagnostic traits such as a descending (but not straight) cingulum and a reciprocal size ratio between episome and hyposome in comparison to the regular form of G. fuscum .